GNAQ and GNA11 mutations occur in 9.5% of mucosal melanoma and are associated with poor prognosis. (September 2016) - Sheng, Xinan; Kong, Yan; Li, Yiqian; Zhang, Qiannan; Si, Lu; Cui, Chuanliang; Chi, Zhihong; Tang, Bixia; Mao, Lili; Lian, Bin; Wang, Xuan; Yan, Xieqiao; et al.
Abstract: Background: Mucosal melanoma (MM) is a rare subtype of melanoma in Caucasians with extremely poor prognosis, and therapy strategy has not been clearly established for MM. We aimed to investigate the genetic aberrations possibly applicable in targeted therapy of MM. We examined the somatic mutations of GNAQ and GNA11 ( GNAQ/11, encoding the guanine nucleotide-binding alpha subunits) in MM and evaluated their correlation to clinicopathologic features of MM. Methods: This study collected samples from primary lesions of 284 MM patients. Tissue samples were analysed for mutations in exons 4 and 5 of GNAQ/11 in genomic DNA by polymerase chain reaction amplification and Sanger sequencing. Correlations of GNAQ / 11 mutations to clinicopathologic features and prognosis of MM were evaluated. Results: The overall mutation frequency of GNAQ/11 in MM was 9.5% (27 in 284), with a frequency of 4.6% and 4.9% for GNAQ and GNA11 mutations, respectively. The mutations in exon 5 of GNAQ/11 occurred exclusively in codon 209. GNAQ Q209L was the most prevalent variation (92.3% of missense GNAQ mutations). GNAQ/11 mutations were not significantly associated with age, gender, ulceration, and primary anatomic site. The median overall survival for MM patients with GNAQ mutations (16.0 versus 26.0 months, P  = 0.031) or GNA11 mutations (15.0 versus 26.0 months, P  = 0.039) were significantly shorter than those for patients with wild-type GNAQ and GNA11, respectively. Conclusions: Our study suggests that GNAQ and GNA11 mutations occur frequently in MM and may be a prognostic factor for MM. Our data implicate that GNAQ/11 may be potential targets for targeted therapy of MM. Highlights: We examine somatic mutations of GNAQ and GNA11 in 284 cases of mucosal melanomas. GNAQ and GNA11 mutations occur frequently in mucosal melanomas. GNAQ and GNA11 mutations are associated with a poor prognosis of mucosal melanomas.